Studi tentang Faktor yang Mempengaruhi Kualitas Hidup Pasien Anak dengan Penyakit Kronis - Wahyuni, Sri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Chronic diseases in children pose a serious challenge in healthcare because they impact not only physical health but also psychological, social, and academic aspects. The quality of life of pediatric patients with chronic diseases is significantly influenced by various factors, including family support, socioeconomic status, medication adherence, and the duration of the child's illness. This study aimed to analyze the factors influencing the quality of life of pediatric patients with chronic diseases at Prof. Dr. Kandou General Hospital in Manado on April 18, 2025. The research method used a quantitative design with a cross-sectional approach. The study sample consisted of 80 children aged 7–17 years with a diagnosis of chronic diseases (cancer, thalassemia, and chronic kidney failure) selected using a purposive sampling technique. The instruments used were the Pediatric Quality of Life Inventory (PedsQL) to assess children's quality of life and supporting questionnaires to measure influencing factors. Data analysis was performed using logistic regression with a significance level of p<0.05. The results showed that the most influential factor affecting children's quality of life was family support (p=0.002), followed by socioeconomic status (p=0.011), and medication adherence (p=0.023). Meanwhile, disease duration did not show a significant effect (p=0.089). The conclusion of this study is that family support is a major factor influencing the quality of life of children with chronic illnesses. Therefore, healthcare interventions should focus on strengthening family support, educating patients about the importance of medication adherence, and providing socioeconomic support to improve children's well-being.